Performance of high-order implicit large eddy simulations. (15th September 2018) - Ritos, Konstantinos; Kokkinakis, Ioannis W.; Drikakis, Dimitris
Highlights: Parallel scalability using up to one billion cells for the Taylor Green Vortex. High-order iLES vs strict DNS: accuracy and computational cost. 9th-order iLES vs 2nd-order iLES: accuracy and computational cost. Abstract: The performance of parallel implicit Large Eddy Simulations (iLES) is investigated in conjunction with high-order weighted essentially non-oscillatory schemes up to 11th-order of accuracy. Simulations were performed for the Taylor Green Vortex and supersonic turbulent boundary layer flows on High Performance Computing (HPC) facilities. The present iLES are highly scalable achieving performance of approximately 93% and 68% on 1536 and 6144 cores, respectively, for simulations on a mesh of approximately 1.07 billion cells. The study also shows that high-order iLES attain accuracy similar to strict Direct Numerical Simulation (DNS) but at a reduced computational cost.